Analysis of the Role of Notaries in Changing a Sole Proprietorship (PT) to a Regular Limited Liability Company (PT) - Nuryana, Nuryana; Hafidz, Jawade (Program Studi Master of Notary Law (S2), Faculty of Law, Universitas Islam SUltan Agung, 2025)
This study aims to analyze: 1)The role of a notary in changing a limited liability company (PT) from an individual to a regular limited liability company (PT). 2). The responsibility of a notary in changing a limited liability company (PT) from an individual to a regular limited liability company (PT). This type of research falls within the scope of normative legal research. The approach method in this research is the statute approach. The type of data in this research is secondary data. Secondary data sources consist of primary, secondary, and tertiary legal materials. The data collection method in this research is using library techniques (document study). The analysis in this research is prescriptive. The results of the research conclude: 1). The role of a notary in changing a limited liability company (PT) from an individual to a regular limited liability company (PT) is the implementation of the attribution authority granted by the state as regulated in Law Number 2 of 2014 concerning the Position of Notary (UUJN). In its implementation, a notary is authorized to make an authentic deed as a legal basis for changing the status of a legal entity, adjusting the articles of association in accordance with Law Number 40 of 2007 concerning Limited Liability Companies, and ensuring that the legal provisions for establishment are met as stipulated in Article 7 paragraph (1) of the PT Law. The notary also plays a role in verifying the data and documents of the parties, preparing a Deed of Statement of Change of Status, and submitting the ratification of the change through the Legal Entity Administration System (SABH) at the Ministry of Law and Human Rights. In addition to being an official who makes the deed, the notary acts as a legal advisor who ensures that the entire process of changing the legal entity runs according to procedure, based on the principle of legal certainty (rechtszekerheid) and orderly administration, so that the resulting deed has binding legal force and protects the legal interests of the parties. 2) The notary's responsibilities in changing an Individual PT into an Ordinary PT include administrative, civil, criminal and ethical aspects, as stipulated in statutory regulations. Notaries are responsible administratively under Article 85 of the UUJN, civilly under Article 1365 of the Indonesian Civil Code, and criminally under Article 266 of the Indonesian Criminal Code, and are required to comply with the Notary Code of Ethics (INI). Legally, these responsibilities reflect the principles of accountability and legal certainty (rechtszekerheid) so that the deeds they create have valid legal force and protect the rights of the parties.